Boundary layer flow, heat and mass transfer of Cu-water nanofluid over a moving plate with Soret and Dufour effects: stability analysis - Najib, Najwa; Bachok @ Lati, Norfifah (Penerbit Akademia Baru, 2021)
Our main focus in this paper is to investigate the effects of Soret and Dufour known as thermodiffusion and diffusion-thermo on moving plate in copper water nanofluid. The set of partial differential equations are converted into set of ordinary differential equations using the appropriate similarity variables before being solved numerically using bvp4c code in Matlab software. The results of heat and mass transfer, temperature and concentration profiles on Soret as well as Dufour effects are presented graphically. Soret effect increases the heat transfer rate at the surface while Dufour effect decreases the mass transfer rate at the surface. Since the solutions exist in dual, we carry out the stability solutions to determine which solution is stable and hence the physical meaning is realized physically.